77. Altered H-reflex following pulsed radiofrequency in patients with lumbosacral radicular pain. Issue 12 (December 2017) - Vigneri, S.; Sindaco, G.; Zanella, M.; La Grua, M.; Pari, G.; Tugnoli, V.
Abstract : Pulsed radiofrequency (PRF) short-lasting bursts allow pain modulation with no tissue necrosis. Neurophysiological evaluation of PRF possible effects has not been described yet. Objective of this study was to investigate the effects of PRF on sensory nerve conduction and H-reflex in patients with lumbosacral radicular pain. We evaluated 23 patients with unilateral L5-S1 root pain who underwent PRF at the corresponding level of radicular symptoms. PRF was applied through a multifunctional electrode introduced via trans-sacral access for 240 s. at a frequency of 2 Hz, amplitude of 45 V and a tip temperature between 40 and 42 °C. Neurophysiological evaluation was performed with the patient lying on a fluoroscopy table in the prone position. Sural sensory action potentials (SAP) and soleus H-reflex were bilaterally evaluated. Outcome measures included variation of sural nerve conduction and H-reflex parameters pre-, post-treatment with PRF and after 30 days from the procedure. P values <0.05 were considered statistically significant. A significant decrease in H/M ratio was observed in the affected side of patients with paresthesia either post-treatment ( p = 0.007) and at one month follow-up ( p = 0.04). PRF might exert its clinical effects beyond DRG through an action on spinal inhibitory interneuronal circuitry.